The Implementation of Asilaty Method in Learning the "Yellow Book" (Kitab Kuning) at Al Isyraq Islamic Boarding School - Ari Khairurrijal Fahmi; Zafa Junarif; Muhammad Fahri (Kalimatuna: Journal of Arabic Research, 2022)
This study examined and explored how the "Asilaty" method is used as a method of learning Arabic with the Yellow Book at Al Isyraq Islamic Boarding School. This study used qualitative research methods with case study techniques. The process of collecting data through informants was carried out such as observation, interviews, and documentation, to get detailed information and descriptions of the analysis of the Asilaty method in learning the Yellow Book at the Al-Isyraq Islamic boarding school, West Jakarta. The results of the study proved that learning to read the Yellow Book using the Asilaty method at Al-Isyraq Islamic Boarding School can be carried out well and effectively and in a short time. This is because the "Asilaty" method has differences from the others, namely the preparation of books that are easy to understand, focus on understanding, and practice the material by always asking questions to all students evenly. In order to do their duties, students are obliged to do muthala’ah, mudzakaroh, takrar.